O ensino do léxico pelo recorte da coesão nominal: uma abordagem das anáforas nominais sob a ótica do interacionismo sociodiscursivo - Maria Bernadete Baggio Rehfeld Santos (2017)
Our research has the nominal cohesion as main topic and investigates it through the nominal anaphoras. Their choice is due to the fact that many researches show that these anaphoras have relevant sociocognitive roles in a text production process because they work for the maintenance of the main topic, for its organization in secondary topics, for the encapsulation and labeling of a propositional content and for marking the point of view of the producer agent as well as of the social voices present in the text, among others. It is anchored in the socio-interactionist conception of language and the way of teach the idiom itself through the teaching of lexicon and also on the Ferraz (2010) method of teaching of lexicon by lexical competence development. It adopts the theoretical assumptions of Sociodiscursive Interactionism (SDI), formulated by Bronckart (1999), according to which written textual production results from the appropriation by the producing agent of a set of sociodiscursive parameters and their mobilization when executing a language action. From this perspective, the researcher must focusing on the sociopsychological conditions of production on first place and then analyze the structural and functional properties of the text. The main goal in this investigation is to explain the difficulty that many students demonstrate as they build up these arrangements, in inappropriate way mostly, as soon as they graduate in primary school. We start from the hypothesis that this difficulty seems to be related to the treatment given to the lexicon in the classroom and, in order to investigate it, we chose as test subjects high school students about to do the vestibular test and, like their corpus, the text produced by them in this situation. It was gathered theoretical-opinion texts from the four major areas of knowledge: Biomedical, Exact, Human and Economics sciences. According to Günther (2005), we collected the data by sampling and interrupted it by the principle of theoretical saturation, of Glaser e Strauss (1967). We started gathering the data through a global reading of the texts following the observation procedure suggested by Bronckart (1999). This procedure involves observables of semantic, lexicon-sintactical and paralinguistic nature. We performed some others readings, focusing ourselves on the observables of lexicon-sintactical nature in order to identify, categorize, quantify and analyze the anaphoric arrangements of each text. The results achieved show the supremacy of the lexical repetition usage and among the resources by lexical variation the ones with synonyms and generic names, nominal core immediately accessible to the producer agent and due to that requiring low cognitive effort on their part. These evidences show the need of an explicit and systematic work in the classrooms during high school, with other resources, once involves specific knowledge that demands from the teacher specific actions on each of them. The results obtained shows that among the coreferencial anaphoras the most used kinds were lexical repetition, sinonyms, generic names which are nominal cores immediately accessible to the producer agent requiring from him low cognitive effort. Among the non-coreferencial anaphoras prevails the meronyms due to the fact that there is a close conceptual relation between an anaphoras and its anchor that leads to no coreference nor retake between them. Regarding the other mechanisms, the findings indicates the necessity of develop an explicit and systematic work in high school having them as the main topic once it requires specific knowledge from the students that will demand the teacher to take accurate actions.